The Effects of Relationship Selling & Promotional Activities on Doctors Practice in Malaysia - Lee, Wei Chiat (2010)
The debate if doctors are affected with interactions with pharmaceutical companies has been ongoing for some time. When we are in our doctor’s clinic, we always see that they own pens or notepads with pharmaceutical company’s branding printed clearly on them. These items clearly are given by medical representatives that so frequently visit doctors. The relationship between doctors and medical representatives is something this research will try to uncover and find out how it affects doctors practice. This study will use a quantitative method which aimed to examine the effects promotional activities and relationship selling on doctor’s practice in Malaysia. The finding of this study indicates that various relationship selling attributes do affect doctor’s practice and promotional activities do play a role as well. Marketing theories related to relationship selling and promotions will form part of the literature review for this study.